MENUMBUHKAN WORK ENGAGEMENT DOSEN DI KOTA SALATIGA DENGAN MEMPERHATIKAN OCCUPATIONAL STRESS DAN DI MEDIASI PSYCHOLOGICAL WELL BEING SAAT PANDEMI COVID-19 - Barkhowa, Mokhammad Khukaim; Widodo, Tri (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
Work engagement is a recent issue in the management of human resources. Work engagement is defined as a positive and satisfying mental state related to work characterized by vigor, dedication, and absorption. The purpose of this study was to analyze the effect of job stress on job involvement through psychological health which is an intervening variable. Sampling in this study using the Slovin formula means 42 respondents. Sampling using incidental sampling combined with snowball sampling techniques. The data analysis used multiple linear regression models, simple linear regression and single test. The results of the hypothesis of work stress have a statistically significant and negative effect on job involvement, psychological well-being has a positive and significant effect on job involvement, job stress has a statistically negative and significant effect on psychological health, job stress has an effect on job involvement through psychological well-being as a variable. intervening.